Preface: 6th International Conference on Art, Design and Cultural Studies (ADCS 2024) - Zhu, Shanhong; Liang, Jiayu (Transactions on Social Science, Education and Humanities Research, 2024)
6th International Conference on Art, Design and Cultural Studies (ADCS 2024) was held during April 13-14, 2024 in Wuhan City, China, and this conference was a great success.The conference provides a useful and wide platform both for display the latest research and for exchange of research results and thoughts in Art, Design and Cultural Studies. The success and prosperity of the conference is reflected high level of the papers received. The aim of ADCS 2024 is to provide a platform for educators, sociologists, designers, writers, historians and graduate students from different cultural backgrounds to present and discuss research, developments and innovations in all fields of Art, Design and Cultural Studies. It provides opportunities for the delegates to exchange new ideas and application experiences, to establish business or research relations and to find global partners for future collaboration.We would like to acknowledge all of those who supported 6th ADCS. Each individual in addition, institutional help was very important for the success of this conference. Especially we would like to thank the organizing committee for their valuable advices in the organization and helpful peer review of the papers.It was a fully synchronized online conference that had live Q&A, participants jointly listened to presentations, and attended other live events associated with the conference. Each speech lasted for 30 minutes, including 5 minutes for Q&A. and for other sessions, there was 20 minutes for each presentation, including 5 minutes for Q&A. The interaction session was made the real experience to the participants and they had good exposure with the foreign university students and delegates.We would like to thank all the author submitted papers to the conferences and thank you all the reviewers for their time and effort in reviewing articles. Finally, it is a great honor to thank you all of behind staff who made their constant effort to make sure the conference process can go smoothly and the proceeding team who have dedicated their constant support and countless time to bring these scratches into this volume.Shanhong Zhu, Jiayu LiangConference Committees